Fatigue assessment of flange connections in offshore wind turbines under the initial flatness divergence - Ji, Xingda; Zou, Tao; Bai, Xu; Niu, Xinbo; Tao, Longbin (Frontiers in Energy Research, 2023)
Bolted ring flange connections are widely utilized in offshore wind turbines to connect steel tubular segments. After the massive production and installation of offshore wind turbines in the past decade, flatness divergence is regarded as one of the most important initial imperfections for the fatigue design of flange connections. Offshore wind turbines are subjected to wind, wave, and current loads. This initial imperfection may alter the structural response and accelerate the fatigue crack growth. This paper aims to analyse the impact of the initial flatness divergence on the structural response of flange connections and evaluate its consequences on fatigue damage. Two different offshore wind turbines with fixed foundations and floating foundations are modelled to simulate their global responses to environmental loads. Based on a superposition method, local finite-element models of flange connections are established with three types of flatness divergence. Using the same bolt pretension and external loads from global modelling, the impact of these geometric imperfections is further examined by comparing the structural responses of flanges under different radial and peripheral opening lengths. Then, the fatigue assessments on flange connections in both fixed wind turbines and floating wind turbines are conducted, and the impacts of initial flatness divergence on these two different wind turbines are analysed.